Adventures in electrochemistry - Morgan, Alfred Powell, 1889-1972. (New York : Scribner, 1977)
Discusses the historical background and present-day importance of electrochemistry and includes instructions for constructing apparatus and performing experiments.
"An updated version of the 1959 ed."
Includes index.
Keywords: Electrochemistry -- Juvenile literature; Electrochemistry